Technical and Economic Analysis for 5G Nr Network Non-Standalone Planning In Yogyakarta City Using 2300 MHz Frequency - Ridho Prasetyo Wicaksono; Ulinuha Mustakim, Hamzah; Ayu Faradila Purnama, Arrizky (Journal of Computer, Electronic, and Telecommunication (COMPLETE), 2024)
Yogyakarta City covers a total area of 32,819 km2 with a population of 378,913 in 2022. Yogyakarta City has the potential to improve connectivity and enhance telecommunication services, which will benefit the population and overall city development. Additionally, the adoption of 5G NR technology can also support various sectors such as education, business, tourism, and governance, benefiting the community and the local economy. Therefore, Yogyakarta City's support for the establishment of 5G NR planning can be explained by the potential benefits offered by the technology in improving the quality of life and overall city development. This research utilizes the Technical Planning of 5G New Radio networks in Yogyakarta City with the architecture of 5G New Radio (NR) in Non-Standalone (NSA) mode. It encompasses technical design aspects related to coverage and capacity, cost planning (NPV, PP, IRR, ROI), and economic analysis (Capex, Opex, and Revenue). In the simulation, coverage for 47 sites was achieved, meeting the criteria for good signal quality, and for capacity, 43 sites with good signal quality were obtained. The cost and economic results obtained over 4 years show that the initial capital will be recouped, indicating that the investment is feasible to proceed with.